Blast test standard adaption for hazard assessment of evolving construction techniques - Laycock, Angela; Hazael, Rachael; Helliker, Aimee; Critchley, Richard (International Test and Evaluation Association (ITEA), 2025)
With constantly evolving building materials and construction techniques due to drivers such as cost, speed of construction, and most recently, climate change, the testing industry must also evolve new standards. This need is especially true for extreme loading cases such as blast hazards and weapons effects on structures, where the focus is on the design of protective buildings, rather than the performance of standard buildings against the effects of accidental or terrorist-related explosive events. Our research study adapts an existing standard for curtain walling to assess the hazards of modular building walls subject to a large free-field blast. It uses the modified standard to assess internal and external hazards and creates novel hazard maps to enable designers and specifiers to compare wall performance against metrics such as Global Warming Potential and thermal transmittance, drivers to achieve net-zero carbon. The research concludes that rapid adaptation of test standards is a useful means of assessing and comparing hazards when no other standards exist, and the approach could be further developed to assess other threat scenarios, including near-field blast and fragmentation effects. This research is of interest to the explosive test community, especially those developing new protective structures or setting test standards.
Keywords: Blast; Explosion; IED; Risk; Low carbon; Blast Protection